Efficacy and safety of tildrakizumab for plaque psoriasis with continuous dosing, treatment interruption, dose adjustments and switching from etanercept: results from phase III studies. (19th November 2019) - Kimball, A.B.; Papp, K.A.; Reich, K.; Gooderham, M.; Li, Q.; Cichanowitz, N.; La Rosa, C.; Blauvelt, A.
Summary: Background: Chronic psoriasis may require medication adjustments over time. Objectives: To evaluate the efficacy/safety of tildrakizumab in subgroups from the reSURFACE studies ( N = 1862) that received continuous dosing, higher/lower dosing, treatment interruption/reinitiation and initiation. Methods: Responders [Psoriasis Area and Severity Index (PASI) ≥ 75%] and partial responders (PASI ≥ 50% to < 75%) in Part 3 of the reSURFACE studies (weeks 28–52 or week 64) who received tildrakizumab 200 mg or 100 mg were rerandomized to the same dosage (T100/T100 or T200/T200), a higher/lower dosage (T100/T200 or T200/T100) or placebo (PBO) (T100/PBO or T200/PBO). Patients receiving PBO who relapsed were reinitiated to tildrakizumab. Etanercept (ETN) week‐28 partial responders and nonresponders (PASI < 50%) received tildrakizumab 200 mg (ETN/T200). Results: Among T100/T100 and T200/T200 week‐28 partial responders, the proportion of patients who achieved as‐observed PASI 75 responses increased over time. Among T100/T200 week‐28 partial responders, PASI 75 responses increased from week 32 (38·5%) to week 52 (63·2%) and remained consistent in T200/T100 week‐28 responders. Among patients who relapsed in the T100/PBO and T200/PBO groups, 86% and 83% of those who reinitiated tildrakizumab achieved PASI 75 by week 64, respectively. Among ETN/T200 week‐28 partial responders, PASI 75 responses (nonresponder imputation) increased from week 32 (24·1%) to week 52 (74·7%). PASI 90, PASI 100 and Physician's Global Assessment responses were consistent with PASI 75 results. Treatment was well tolerated. Conclusions: Patients generally fared well with tildrakizumab maintenance, reinitiation, dose adjustment or initiation. What's already known about this topic? Tildrakizumab demonstrated significant efficacy vs. placebo with a positive safety profile during the first 28 weeks of treatment in two randomized double‐blind trials. What does this study add? Treatment scenarios with tildrakizumab, such as long‐term continuous dosing (up to 64 weeks), treatment interruption/reinitiation and switching from another biologic, can be part of the management of plaque psoriasis with a reasonable expectation of efficacy and tolerability. Abstract : Plain language summary available online Respond to this article